The Effect of Relaxation Therapy on Hypoxia During Intravenous Propofol Anesthesia in Patients With Pre-operative Anxiety: A Prospective Randomized Controlled Trial - Fang, Yiling; Jing, Qi; Cao, Silu; Sun, Xiaoru; Zhang, Hui; Tian, Li; Li, Cheng (Frontiers in Medicine, 2022)
Background This study aimed to investigate the effect of relaxation therapy on hypoxia during intravenous propofol anesthesia in patients with pre-operative anxiety. Methods Two-hundred and eighty patients were randomly categorized in the experimental group (relaxation therapy group) and control group. The Spielberger State-Trait Anxiety Inventory (S-STAI) was administered 30 to 60 min pre-operatively to assess the patient's current anxiety status and select appropriate patients. Patients in the experimental group received pre-surgical relaxation therapy. Decrease in oxygen saturation during the procedure was recorded for each patient group, and the relevant data were compared between the two groups. Results The basic S-STAI scores of the experimental and control groups were 56.88 ± 2.91 and 57.27 ± 3.56, respectively (p = 0.331). The difference was not statistically significant. The incidence of hypoxia in the experimental group during painless artificial abortion [routine blood oxygen saturation (SpO2) <95%, duration >15 s] decreased from 30 to 12.3%. Conclusion Relaxation therapy may effectively reduce the incidence of hypoxia during painless artificial abortion by using less dose of propofol. It may help patients relieve their anxiety and improve perioperative safety. Trial Registration Chinese Clinical Trial Registry (ChiCTR2000032109).